Perancangan Sistem Informasi Akuntansi penggajian dengan mengunakan Microsoft Visual Basic 2008 dan database MySQL - Dwi Puspa Lestari (Labkat Press KA FTIK UNIKOM, 2017)
KSP.Kopdit Borromeo is a company engaged in the service. In KSP. Kopdit Borromeo who is responsible for the performance of employees in a company which is part of the manager. The author conducted research on the treasurer in charge of payroll employees. But the company still uses KSP.Kopdit Borromeus payroll manually, ie by using Microsoft Excel. To reduce the existing problems, the authors take the title